BUDGET MASTER: NLP BASED SMS ANALYSIS AND EXPENSE TRACKING (CAHIERS MAGELLANES-NS, 2024)
Nowadays expense tracking is very important, as demand of automated expense tracking is increasing, so traditional methods of expense tracking seem outdated.To avoid manual input labor, we are providing an efficient method to do the same work, which will take less time by help of SMS Tracking.This software reduces human effort and provide the easy way to track the expense and provide good data insights.It tracks expense by using NLP on transaction SMS. It provides several advantages for businesses also. This software helps to control unnecessary expenses. By using graphs to represent data, this app helps users to track their money to identify financial issues for future.